Rancang Bangun Sistem Informasi Pendaftaran Peserta Didik Baru Berbasis Website di SMK Harapan 2 Rancaekek - Rahman, Widi Widya; Supriatna, Encep (Jurnal Dimamu, 2024)
The development of the internet from year to year is increasingly experiencing a very rapid spread. The benefits of the internet can also be felt in the field of education where the internet can help all activities in the field of education to make it easier and faster, one of which is the process of accepting new students. In this study it was found that the system used in accepting new students was still manual and did not work well. Referring to the research objectives and the results of observations made, the solution to overcome this problem is to create a new system to solve existing problems.the design uses the Object Oriented Analysis and Design (OOAD) method using the Rational Unified Process (RUP) system design. The results showed that design of a new student registration information system is able to improve the delivery of information, provide services quickly and as a medium for school promotion.